(untitled) (Revista da Faculdade de Odontologia - UPF, 2014)
Objective: this study aimed to assess the radiopacity of eight composite resins recommended for class II restorations. Materials and method: hence, 2 mm thick and 4 mm in diameter test specimens were made and compared to enamel, dentin, and aluminum using four digital systems: two semi-direct by storage phosphor image plates (SPIP) - Digora™, and DenOptix™, two charged couple devices (CCD) - Sens-A-Ray™ and Computerized Dental Radiograph (CDR™), and radiographic film Kodak Insight IS-21™. The radiographs were scanned to obtain the indirect digital image, and along with direct and semi-direct digital images the radiographic densities were assessed in specific software. The pixel values from the aluminum step wedge were submitted to a linear regression from where the equivalent in millimeters for enamel, dentin, and resins were determined. Results: density means of resins were equal or superior to the means obtained for enamel in all digital systems and the conventional film. SureFil™ resin presented greater numerical radiopacity in all digital systems and the radiographic film. ALERT™ resin showed the smallest radiopacity among the studied resins in all digital systems and radiographic film. ALERT™ and Definite™ were statistically equivalent to enamel in the Sens-A-Ray™ system and in radiographic film. The remaining resins (Charisma™, FillMagic™, P60™, Prodigy™, SureFil™, and Z250™) presented higher radiopacities in comparison to enamel. Only ALERT™ presented radiopacity similar to enamel in other digital systems (CDR™, DenOptix™, and Digora™). In these digital systems, Charisma™, Definite™, FillMagic™, P60™, Prodigy™, SureFil™, and Z250™ were more radiopaque than enamel. Conclusion: all resins showed equal or higher radiopacities of enamel in all assessment systems. There was a statistical correlation between systems CDR™ and Sens-A-Ray™, and between Digora™ and DenOptix™; Sens-A-Ray™ also showed correlation with radiographic film. The percentage of density means equivalent to aluminum millimeters for enamel and dentin were 119.6% and 101.6%, respectively.